Development of a new part of casing cap for the parking brake cable using finite element analysis - Buthgate, Siwawong; Saenthon, Anakkapon; Kaitwanidvilai, Somyot (My University, 2017)
The brake system is an important safety system in every vehicle. This system is utilized for controlling of the vehicle movement. This paper proposes a new design and development of casing cap for the parking brake cable by applying the finite element technique to analyzing and evaluating the feasibility of the material and the design of the product. The study and analysis of influential factors affecting the parts of casing cap by JASO standard F903-75 control cable for automobiles are described. The results show that the plastic PA GF15 can be used to replace the conventional material that is steel casing cap, and will then be able to reduce the overall cost material by 2.5%. In addition, the results of the analysis illustrate that all features of the new product are complied with JASO F903-75, the control cable standard for vehicles.
Keywords: Casing cap of the parking brake cable; Finite element method; JASO F903-75 control cable for automobiles; Plastic PA GF15